Study of the response characteristics of the water–force coupling action of hard coal bodies in steeply inclined coal seams - Zhang, Leiming; Lai, Xingping; Bai, Rui (Frontiers in Earth Science, 2023)
Study of the pre-blast weakening of hard-top coal water injection is especially important to solve problems related to the low recovery rate of coal resources and frequent dynamic disasters due to the low degree of fragmentation of hard-top coal during high-stage fully mechanized top-coal caving in steeply inclined coal seams. With the application of rock mechanical tests and numerical simulations, this study carries out mechanical property testing on natural and water-saturated coal samples, investigates the effect of moisture on coal sample mechanical properties in meso-scale, and quantifies the degradation of coal samples under moisture due to mollification. It also reveals the interaction between water and acoustic emission signals based on the statistics of acoustic emission count and energy. A numerical model is established to analyze coal sample internal stress distribution features before and after water injection in macro-scale. Moreover, the detailed mitigating measures for top-coal water injection for engineering practice are designed. The results demonstrate that the mechanical properties of coal samples are significantly affected by moisture-induced degradation. The failure and collapse degrees of water-saturated samples are generally larger than those of natural samples. When the water content is higher, the acoustic emission count and energy of the coal sample are smaller—presenting a negative correlation. The internal stress of coal samples before and after water injection differs significantly. When subjected to water, the top-coal stress releases and transfers, and the peak value is significantly reduced. This study has verified in macro- and meso-scales that top coal can be fully weakened under water–force coupling. The findings of this study are of practical significance for safe and efficient mining and provide a reference for presplit weakening of hard-top coal during horizontal sublevel fully mechanized top-coal caving in steeply inclined coal seams.